FILSAFAT PENDIDIKAN SEBAGAI KONSEP PENGEMBANGAN KURIKULUM PENDIDIKAN SENI DI INDONESIA - Iwan Pranoto; Ediantes Ediantes; Vitta Diana Siahaan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Educational philosophy is an important idea in the development of learning, especially the educational curriculum. This is an important bridge so that the direction of education becomes clearer to make an achievement. One of the most important parts is the development of the concept of an arts education curriculum which refers to several understandings in an educational philosophy. The development of an arts education curriculum includes several important streams such as philosophical, juridical, empirical foundations, with perennialism, essentialism, progressiveism, and reconstructiveism. The development of the art education curriculum aims to respond to the journey of art education in Indonesia. This is related to the function of the curriculum, its objectives, meaningfulness, benefits, parameters, achievements, and further development of art learning in Indonesia. In this study using a qualitative description method, by collecting data including interviews, literature studies, and observations, important sources in this study include the thoughts of art education developers, schools and communities, which are then matched with understandings of the arts education curriculum. The results of this study reveal the school of educational philosophy in looking at the development of the arts curriculum, both in its development, application, evaluation and subsequent development processes. Another thing is that the aspect of art education is an important part when viewed from the approach and understanding of educational philosophy in Indonesia. This reveals the achievements of each era and period of educational curriculum development as a basis for shaping art learning in formal schools in Indonesia.